Supersulfide formation in the sinus mucosa of chronic rhinosinusitis - Jun Suzuki; Tomotaka Hemmi; Tomoaki Ida; Seiryo Ogata; Jun Yoshitake; Tetsuro Matsunaga; Tomoyasu Ishida; Yuki Numano; Yusuke Kusano; Ryoukichi Ikeda; Kazuhiro Nomura; Mitsuru Sugawara; et al. (Laryngoscope Investigative Otolaryngology, 2024)
Abstract Objectives Disruption of the oxidative stress defense system is involved in developing various diseases. Sulfur compounds such as glutathione (GSH) and cysteine (CysSH) are representative antioxidants in the body. Recently, supersulfides, including reactive persulfide and polysulfide species, have gained attention as potent antioxidants regulating oxidative stress and redox signaling. However, their involvement in the pathogenesis of chronic rhinosinusitis (CRS) remains unclear. Methods To clarify the changes in sulfur compounds within the sinus mucosa of each CRS subtype, we measured sulfur compound levels in the sinus mucosa of control individuals (n = 9), patients with eosinophilic CRS (ECRS) (n = 13), and those with non‐ECRS (nECRS) (n = 11) who underwent sinus surgery using mass spectrometry. Results GSH and CysSH levels were significantly reduced, and the glutathione disulfide (GSSG)/GSH ratio, an oxidative stress indicator, was increased in patients with ECRS. Despite the absence of notable variations in supersulfides, patients with ECRS and nECRS exhibited a significant reduction in glutathione trisulfide (GSSSG), which serves as the precursor for supersulfides. Conclusions This study is the first quantitative assessment of supersulfides in normal and inflamed sinus mucosa, suggesting that sulfur compounds contribute to the pathogenesis of CRS. Level of Evidence N/A.